Apart : towards the dissolution of the negative dialectic found in artistic exhibition through the adaptive reuse of the Sunnyside Post Office into an art complex - Van der Wath, Elana (University of Pretoria, 2015)
Dissertation (MInt(Prof))--University of Pretoria, 2014.